2022
DOI: 10.3389/fonc.2021.773186
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Anti-Tumor Effect of Combining Selective CDK7 and BRD4 Inhibition in Neuroblastoma

Abstract: PurposeCyclin-dependent kinases (CDKs) that have critical roles in RNA polymerase II (Pol II)-mediated gene transcription are emerging as therapeutic targets in cancer. We have previously shown that THZ1, a covalent inhibitor of CDKs 7/12/13, leads to cytotoxicity in MYCN-amplified neuroblastoma through the downregulation of super-enhancer-associated transcriptional upregulation. Here we determined the effects of YKL-5-124, a novel covalent inhibitor with greater selectivity for CDK7 in neuroblastoma cells.Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…PROTACs are heterobifunctional molecules that can ubiquitinate and degrade target proteins by recruiting E3 ligases to target proteins. It precisely targets BRD4 proteins, induces the degradation of BRD2 and BRD3, and has a strong antitumor effect on neuroblastoma [20]. In order to evaluate the anti-NB effect of dBET57, NB cells and 4 normal cells were treated in a concentration gradient for 72 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PROTACs are heterobifunctional molecules that can ubiquitinate and degrade target proteins by recruiting E3 ligases to target proteins. It precisely targets BRD4 proteins, induces the degradation of BRD2 and BRD3, and has a strong antitumor effect on neuroblastoma [20]. In order to evaluate the anti-NB effect of dBET57, NB cells and 4 normal cells were treated in a concentration gradient for 72 hours.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically, BRD4 inhibitors targeting ubiquitin-mediated hydrolysis of MYCN to treat NB have important significance and application prospects. In recent years, clinical trials of BRD4 inhibitors have shown that early acquired resistance limits their therapeutic benefits [20]. In this study, we investigated dBET57, a heterobifunctional molecule inhibitor that binds the target protein at one end and the E3 ubiquitin ligase (CRBN binding fragment) at the other end.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the RNA Pol2 loading ratio, but not the pausing ratio, suggests a separate mechanism from CDK9. CDK7 phosphorylates serine 5 of Pol2 at the promoter to promote initiation [ 32 ], and it has been shown that CDK7 inhibitors have a synergistic effect when combined with BRD4 inhibitors in neuroblastoma [ 33 ], so a local increase in CDK7 could also be implicated. Another possibility is that BRD4 at super enhancers is involved in the unloading of Pol2 during termination.…”
Section: Discussionmentioning
confidence: 99%
“…THZ2 has improved pharmacokinetic features compared with THZ1, with a 5-fold improved half-life in vivo [ 238 ]. Some other CDK7 inhibitors, for example, SY-1365 and YKL-5-124, show covalent binding to CDK7 and also have low IC50 and positive effects in ovarian and breast cancer, and neuroblastoma, respectively [ 240 , 241 ] ( Table 3 ). SY-1365 clinical studies are terminated due to business decisions (NCT03134638).…”
Section: Anti-se Drugsmentioning
confidence: 99%